Influence of SPD on Whiteness value of FWA treated samples - Vik, Michal; Viková, Martina; Prince Periyasamy, Aravin (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
The Whiteness of textiles, plastics, paper and paints is important aspects, which are considered in daily life. Customers usually prefer white products, especially in summer because of comfort reasons. In addition, white, being an achromatic color has a physiological effect on human sensation. Generally, High whiteness is not possible to get through only bleaching process. Therefore, the application of FWA’s (Fluorescence Whitening Agents) is a common practice in industry where the need to achieve “high” whiteness. In the case of white materials, the nature of these chemicals is to absorb light in the invisible, or near ultra-violet, region of the spectrum and then re-emit this light as fluorescence in the visible region of the spectrum. This re-emitted light generally occurs between 420-500nm. The effect is a greater degree of reflectance in the blue region of the spectrum, therefore a “bluer” white. In effect, this process produced much whiter whites! Consequently to other color attributes of an object depends on many factors, such as lighting (illumination), size of sample, and background and surrounding colors. Much more importantly, color is a subjective phenomenon and depends on the observer. In this article were discussed the influence of SPD (Spectral Power Distribution) tested light sources on whiteness. Solid-state lighting (white LEDs, etc.) is necessary to improve by a full-visible-spectrum technology because standard white LEDs are unable to activate FWA’s sufficiently. Ra does not capture this issue or other conventional color rendition metrics, although it corresponds to a very large color distortion for shades of white. Full-visible-spectrum LEDs emit no harmful ultra-violet light, but enough violet light to properly excite FWA’s and render whites like natural sources.
Spektrální distribuce použitých světelných zdrojů a hodnota bělosti FWA vzorků
Keywords: Colorimetry; whiteness; spectral power distribution; LED